Passive Aerial Grasping of Ferrous Objects. Issue 1 (July 2017) - Fiaz, Usman A.; Toumi, N.; Shamma, Jeff S.
Abstract: Aerial transportation is probably the most efficient way to supply quick and effective aid especially in cases of emergency like search and rescue operations. Thus the ability to grasp and deliver objects is of vital importance in all sorts of unmanned and autonomous aerial operations. We detail a simple yet novel approach for aerial grasping of ferrous objects using a passive magnetic pickup and an impulse based drop mechanism. The design enables our gripper to grasp ferrous objects using single as well as multiple gripping pads, with visual as well as pickup and drop feedback. We describe the various components of the gripper with emphasis on its low mass and high lift capability since weight is a matter of high consideration in all aerial applications. In addition, we investigate and address the issues that may cause our design to fail. We demonstrate by experiments that the proposed design is robust and effective, based on its high payload capability, its sturdiness against possible slide during aggressive aerial maneuvers, and optimum performance of the drop mechanism for the designed range of payloads. We also show that the gripper is able to pick up and drop a single as well as multiple ferrous objects of different shapes, curvature, and inclination, which also involves picking up an object and then grasping the next, while keeping hold of the previous one.